The Rising Tide and Development of Indian Economy through Service Sector - Gera, Navneet; Kaur, Jasveen (Gyan Management Journal, 2012)
Indian economy has been moving ahead with the service sector as the power house and comprises of about 55% in the overall GDP of the economy. Indian economy has been changing from agro-based economy towards the manufacturing and thereafter towards the service sector economy over a period of years. The research paper aims to investigate the composition of service sector in Indian economy. The research paper will also identify the real reasons for growth in Indian service sector. The research paper aims to study the contribution of the economic reforms in different sectors. The service sector of India has been compared to the developed economies and economies having substantial share in service sector to understand the difference in terms of rankings. The role of Government and measurement issues has been addressed in the research paper.